Appropriate whole genome amplification and pathogenic loci detection can improve the accuracy of preimplantation genetic diagnosis for deletional α-thalassemia - Lan, Yueyun; Zhou, Hong; He, Sheng; Shu, Jinhui; Liang, Lifang; Wei, Hongwei; Luo, Jingsi; Wang, Caizhu; Zhao, Xin; Qiu, Qingming; Huang, Peng (Frontiers in Endocrinology, 2024)
Abstract Objective: To improve the accuracy of preimplantation genetic testing (PGT) in deletional α-thalassemia patients. Design: Article Patient(s): fifty-two deletional α-thalassemia couples. Intervention(s): Whole genome amplification (WGA), Next-generation sequencing (NGS) and PCR mutation loci detection. Main Outcome Measures: WGA, Single nucleotide polymorphism (SNP) and PCR mutation loci detection results; Analysis of embryo chromosome copy number variation (CNV). Results: Multiple Displacement Amplification (MDA) and Multiple Annealing and Looping–Based Amplification Cycles (MALBAC) methods for PGT for deletional α-thalassemia. Blastocyst biopsy samples (n = 253) were obtained from 52 deletional α-thalassemia couples. The results of the comparison of experimental data between groups MALBAC and MDA are as follows: (ⅰ) The average allele drop-out (ADO) rate, MALBAC vs. MDA = 2.27% ± 3.57% vs. 0.97% ± 1.4%, P=0.451); (ⅱ) WGA success rate, MALBAC vs. MDA = 98.61% vs. 98.89%, P=0.851; (ⅲ) SNP haplotype success rate, MALBAC vs. MDA = 94.44% vs. 96.68%, P=0.409; (ⅳ) The result of SNP haplotype analysis is consistent with that of Gap-PCR/Sanger sequencing results, MALBAC vs. MDA = 36(36/72, 50%) vs. 151(151/181, 83.43%), P=0; (ⅴ) Valid SNP loci, MALBAC vs. MDA = 30 ± 9 vs. 34 ±10, P=0.02; (ⅵ) The mean CV values, MALBAC vs. MDA = 0.12 ± 0.263 vs. 0.09 ± 0.40, P=0.916; (ⅶ) The average number of raw reads, MALBAC vs. MDA =3244259 ± 999124 vs. 3713146 ± 1028721, P=0; (ⅷ) The coverage of genome (%), MALBAC vs. MDA = 5.02 ± 1.09 vs. 5.55 ± 1.49, P=0.008. Conclusions: Our findings indicate that MDA is superior to MALBAC for PGT of deletional α-thalassemia. Furthermore, SNP haplotype analysis combined with PCR loci detection can improve the accuracy and detection rate of deletional α-thalassemia.